2012
DOI: 10.1098/rsta.2011.0234
|View full text |Cite
|
Sign up to set email alerts
|

The water vapour self- and water–nitrogen continuum absorption in the 1000 and 2500 cm −1 atmospheric windows

Abstract: The pure water vapour and water-nitrogen continuum absorption in the 1000 and 2500 cm −1 atmospheric windows has been studied using a 2 m base-length Whitetype multi-pass cell coupled with a BOMEM DA3-002 Fourier transform infrared spectrometer. The measurements were carried out at the National Institute of Standards and Technology (NIST, Gaithersburg, MD) over the course of several years (2004,(2006)(2007) 2009). New data on the H 2 O:N 2 continuum in the 1000 cm −1 window are presented and summarized along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 37 publications
6
22
0
7
Order By: Relevance
“…Although there is a general dearth of continuum measurements with which to compare, the CAVIAR self‐ and foreign‐ continua in the 3.8 µm window measurements agree, within the uncertainties, with the laboratory measurements of Baranov () and Baranov and Lafferty (), as well as with some earlier self‐continuum measurements reported in Ptashnik et al (); the older measurements of Burch and Alt () are lower than the newer laboratory measurements in the centre of the window by a factor of about 6 at near‐room temperature (and are lower than the empirically adjusted MT_CKD_2.5 by around a factor of 3), but are in much better agreement at higher temperatures. In the 2.1 and 3.8 µm windows, measurements involving some of the CAVIAR authors, but made using somewhat different experimental set‐ups to those used in CAVIAR (all used the same type of Fourier Transform Spectrometer, but different long and short pathlength gas cells are used), support the CAVIAR results (Paynter et al , ; Ptashnik et al , ), although they are higher than the Bicknell et al () measurements in the centre of the 2.1 µm window by about a factor of 4.…”
Section: Introductionsupporting
confidence: 77%
“…Although there is a general dearth of continuum measurements with which to compare, the CAVIAR self‐ and foreign‐ continua in the 3.8 µm window measurements agree, within the uncertainties, with the laboratory measurements of Baranov () and Baranov and Lafferty (), as well as with some earlier self‐continuum measurements reported in Ptashnik et al (); the older measurements of Burch and Alt () are lower than the newer laboratory measurements in the centre of the window by a factor of about 6 at near‐room temperature (and are lower than the empirically adjusted MT_CKD_2.5 by around a factor of 3), but are in much better agreement at higher temperatures. In the 2.1 and 3.8 µm windows, measurements involving some of the CAVIAR authors, but made using somewhat different experimental set‐ups to those used in CAVIAR (all used the same type of Fourier Transform Spectrometer, but different long and short pathlength gas cells are used), support the CAVIAR results (Paynter et al , ; Ptashnik et al , ), although they are higher than the Bicknell et al () measurements in the centre of the 2.1 µm window by about a factor of 4.…”
Section: Introductionsupporting
confidence: 77%
“…For example, Paynter and Ramaswamy [] showed that the water vapor continuum could result in between 1.1 W m −2 and 3.2 W m −2 additional clear‐sky absorption of solar radiation globally. This sizable range is due to fairly large measurement uncertainties in the shortwave near‐infrared window regions [ Ptashnik et al ., , , , ; Paynter et al ., , ; Baranov and Lafferty , , ; Mondelain et al ., ]. These uncertainties along with a comprehensive history of the water vapor continuum in both the longwave and shortwave has previously been described by Shine et al .…”
Section: Introductionmentioning
confidence: 99%
“…New laboratory measurements of the continuum owing to water-air mixtures in the near-infrared windows by Ptashnik et al [4] indicate that absorption is up to about 100 times stronger than given by the semi-empirical models. Baranov & Lafferty [5] present new observations of the continuum at 4 and 10 mm; while the differences with the semi-empirical models are greatest at the shorter wavelengths, the work stresses that, even in the better characterized mid-infrared region, the semi-empirical models still do not fully reproduce the observed spectral and temperature dependence.…”
Section: Water In the Gas Phasementioning
confidence: 96%